Resetting of the Baroreflex Control of Sympathetic Vasomotor Activity during Natural Behaviors: Description and Conceptual Model of Central Mechanisms - Dampney, Roger A. L. (Frontiers in Neuroscience, 2017)
The baroreceptor reflex controls arterial pressure primarily via reflex changes in vascular resistance, rather than cardiac output. The vascular resistance in turn is dependent upon the activity of sympathetic vasomotor nerves innervating arterioles in different vascular beds. In this review, the major theme is that the baroreflex control of sympathetic vasomotor activity is not constant, but varies according to the behavioural state of the animal. In contrast to the view that was generally accepted up until the 1980s, I argue that the baroreflex control of sympathetic vasomotor activity is not inhibited or overridden during behaviours such as mental stress or exercise, but instead is reset under those conditions so that it continues to be highly effective in regulating sympathetic activity and arterial blood pressure at levels that are appropriate for the particular ongoing behavior. A major challenge is to identify the central mechanisms and neural pathways that subserve such resetting in different behaviours. A model is proposed that is capable of simulating the different ways in which baroreflex resetting is occurred. Future studies are required to determine whether this proposed model is an accurate representation of the central mechanisms responsible for baroreflex resetting.